Land Trafficking, Migration, and Conservation in the "No-Man's Land" of Northeastern Peru. (December 2016) - Shanee, Noga; Shanee, Sam
Peru and especially its northeastern regions are considered a global conservation priority because of high biodiversity and the acute threats they face. Despite the Peruvian state's declared intention to end forest loss, deforestation is on the rise. This is in part due to rural–rural and urban–rural migration to forest frontier zones. This migration is often organized and led by land traffickers. In this article, we use ethnographic methods and case studies to identify major land trafficking types, the interactions between traffickers and local communities, and conservation initiatives as well as authorities' capacity to respond to this illicit practice. Land trafficking exists at different scales and can be highly lucrative. Loopholes in Peruvian laws, conflicting policies, and institutional inefficiencies impede effective confrontation of land trafficking and in some cases even encourage it. Corruption plays an essential role in facilitating this trade. Although local people are often aware of the problems related to land trafficking, their ability to control it is greatly impeded by social factors and by the dangers of confronting organized criminals. Land trafficking is seldom studied but has great environmental and social implications and must be addressed both on academic and practical levels in order to confront biodiversity loss related to migration to forest frontiers.